Formation and Growth Mechanism of Laminar Cu6Sn5 with Ultrafine Grains on Nanocrystalline Cu by Interfacial Reaction with Sn. Issue 27 (26th August 2022) - Chen, Shi; Ren, Xiaolei; Qiao, Yuanyuan; Du, Yanfeng; Lai, Yanqing; Zhao, Ning
Abstract: Cu6 Sn5 intermetallic compound (IMC) formed at Sn/polycrystalline Cu interface after liquid–solid reaction generally presents scallop‐like morphology and tends to ripen into large‐sized grains with texture feature. In this paper, the formation of laminar Cu6 Sn5 on nanocrystalline (NC) Cu by interfacial reaction with liquid Sn is reported. The laminar Cu6 Sn5 consists of stacked ultrafine grains, thickened in the manner of "nibbling" the NC Cu and shows randomly distributed orientations. With extended reaction time, the top Cu6 Sn5 grains that are exposed to the liquid Sn transform into long‐rod‐like grains all along their <0001> direction, while the bottom Cu6 Sn5 grains remain laminar and ultrafine. The formation and growth mechanism of the novel laminar Cu6 Sn5 at the Sn/NC Cu interface as well as that of the rod‐like Cu6 Sn5 are revealed from the aspects of atomic diffusion, nucleation, and grain merging. It is also found that the Cu3 Sn IMC generated at the laminar Cu6 Sn5 /NC Cu interface is much thinner than that at the classic scallop‐like Cu6 Sn5 /polycrystalline Cu interface, showing no obvious formation of Kirkendall voids. Abstract : Formation of laminar Cu6 Sn5 on nanocrystalline (NC) Cu by interfacial reaction with liquid Sn is reported in this article. The laminar Cu6 Sn5 consists of stacked ultrafine grains, thickened in the manner of "nibbling" the NC Cu and shows randomly distributed orientations.